POROUS BASED IMMUNOSENSOR FOR DETECTION OF LDL MOLECULES FROM BLOOD SERUM USING ARRAY OF CANTILEVER BEAM - Research Scholar, Mr.S.Praveenkumar1, Dr.R.Ramesh2, Mr.T.A (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
In this work, the NiO thin film based array of Cantilever structure for the detection of low-density lipoprotein (LDL) is proposed. To detect the LDL molecules in the applied blood serum, the highly selective Anti-apolipoprotein B (AAB-100) act as the phosphate buffer solution (PBS) and it is coated at the tip of the porous NiO thin film based array of cantilever beam. The diffusion length and deflection of cantilever beam are analyzed for the different loads. Presence of five LDL molecules will make the displacement of 3.089e-4 Î¼m. While the amount of LDL molecule is increased, the displacement also gets increased.Â Â